Identification of non-specific tactical tasks in invasion games - Memmert, Daniel; Harvey, Stephen (Physical education and sport pedagogy, 2010)
Background and significance: The notion of transferability (i.e. sampling) has been put forward as one of four core pedagogical principles for games teaching. The sampling principle was based on the premise that it may be possible to show the existence of tactical similarities between apparently dissimilar games, leading to a much better overall understanding of games. However, research has yet to empirically identify tactical problems that are non-specific. This means that they are not specific to any one game, and commonly occur across all invasion games (i.e. soccer, team handball, field hockey) which involve different techniques or skills. Thus, the non-specific framework suggests that unlike motor competencies, it may be possible to train tactical transfer independently of particular movement techniques. A deeper understanding of which kinds of non-specific tactical tasks exist in invasion games would aid teachers and coaches in structuring invasion game units/lessons according to tactical content while offering a variety of games experiences to young children and may further provide a setting in which to assess game performance. While the concept of tactical transfer has been empirically tested in two studies in net/wall game contexts there has been little empirical evaluation of tactical transfer in invasion games, especially for young children (i.e. under 8 years). Purposes: The purpose of this exploratory study was to empirically identify non-specific tactical tasks in invasion games. Design and procedure: In a cross-sectional design 95 children (29 girls, 66 boys; Mage = 6.5 years; SD = .95) participated in various ‘Game Test Situtations’ (n = 7) with different motor executors (n = 3; hands, feet and with an implement). The seven Game Test Situations were situated tactical tasks focused on solving a particular tactical problem. These were: (1) attacking the goal, (2) taking ball near goal, (3) playing together, (4) identification of gaps, (5) feinting, (6) achieving an advantage, and (7) supporting and orienting. Video recordings of Game Test Situations were reviewed by experts and a performance score attributed to each participant for each of the seven GTS with each of the three motor executors (n = 21). These data were placed into the internal structure of an Analysis of Moment Structures (AMOS) model for subsequent factorial validation. Results: Results showed the existence of six non-specific tactical tasks as achieving an advantage and supporting and orientating were found to be the same tactical task. Discussion: Six tactical core tasks were factorially validated. This has pedagogical implications for teaching and coaching in invasion games. Firstly, ‘getting the game right’ allowed the children to exploit the structure of the game in order to use it to make appropriate decisions during their participation in the tactical tasks no matter of the motor executor used. Secondly, deliberate play experiences such as the child's participation in the six tactical tasks at a non-conscious and embodied level may provide an important foundation for future learning. Thirdly, the six tactical tasks may be used by teachers and coaches as a way of assessing game performance. Conclusion: Non-specific tactical tasks such as the six validated in this study offer teachers and coaches a way of taking advantage of the tactical similarities between invasion games which involve different techniques and skills.